2002
DOI: 10.1159/000065588
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Importance of Proton Pump Inhibitor Pharmacokinetics

Abstract: Achieving the optimal clinical response for patients with upper gastrointestinal peptic disease is important. This response depends on the pathology treated as well as on the choice of proton pump inhibitor. Here, we identify factors in specific disease therapy and proton pump inhibitor (PPI) pharmacokinetic and pharmacodynamic characteristics that help us achieve this goal. These include differences in PPI bioavailability and acid-suppressive effects. Available data indicate that PPIs appear to have similar p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
1
32
0
1
Order By: Relevance
“…Collectively, the data support better outcomes in management of GERD and higher success rate of H. pylori eradication in IM and PM phenotypes compared to NM, RM, and UM phenotypes (Table 4) [59,60,6264], which is consistent with the higher intragastric pH achieved in patients with reduced CYP2C19 activity and higher PPI concentrations [7779]. While many studies suggest this to be true regardless of the PPI used, some reports have suggested that the therapeutic outcomes are less influenced by genotype in PPIs with less dependence on CYP2C19 metabolism, namely rabeprazole and esomeprazole [71,73,80].…”
Section: Cyp2c19 and Ppi Pharmacogeneticssupporting
confidence: 59%
“…Collectively, the data support better outcomes in management of GERD and higher success rate of H. pylori eradication in IM and PM phenotypes compared to NM, RM, and UM phenotypes (Table 4) [59,60,6264], which is consistent with the higher intragastric pH achieved in patients with reduced CYP2C19 activity and higher PPI concentrations [7779]. While many studies suggest this to be true regardless of the PPI used, some reports have suggested that the therapeutic outcomes are less influenced by genotype in PPIs with less dependence on CYP2C19 metabolism, namely rabeprazole and esomeprazole [71,73,80].…”
Section: Cyp2c19 and Ppi Pharmacogeneticssupporting
confidence: 59%
“…Finally, we performed multiple dose-response studies using multiple PPIs to show that the various biological responses are present at a range of doses. Importantly, the doses we used are in the micromolar range; these doses were chosen because the PPIs are found in the circulation at these concentrations, [35][36][37] thus we anticipate that this will be the range that is clinically effective. It may be worthwhile undertaking further in vitro studies using drug doses within the nanomolar range as these might shed further clues as to the mechanisms by which PPIs are exerting the diverse biological effects we have observed.…”
Section: Discussionmentioning
confidence: 99%
“…30) Products on the market for the treatment of gastric ulcers, including antacids, proton pump inhibitors, anticholinergic, and histamine H 2 -antagonists, can produce several adverse reactions. 31) Brazil has abundant biodiversity still underexplored. Based on a previous survey, in this work we investigated the effect of extracts of A. glandulosa on gastric lesions induced by several agents.…”
Section: Resultsmentioning
confidence: 99%